PENGARUH LINGKUNGAN BELAJAR SEKOLAH DAN MOTIVASI BELAJAR TERHADAP KEMANDIRIAN BELAJAR PENDIDIKAN AGAMA ISLAM SISWA SD NEGERI 14 BENGKULU SELATAN - Erlina Zanita (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
This research  is motivated by the independence of learning that is realized by every student,  but this is not optimal, especially in learning Islamic Religious Education. The role of school learning environment is very influential on the success of the learning process,  in addition  to the low learning motivation to be one of the factors that make students  have  not achieved the independence of learning Islamic Education maximum. The purpose of this research  is first to know the influence of school learning  environment to the independence of learning  Islamic Religious Education to students  in SD Negeri 14 Bengkulu  Se- latan,  secondly to know the influence of learning motivation to self-reliance learning Islamic Religion on students  at SD Negeri14  Bengkulu  Selatan, third  to know  A simultaneous positive  influence  between  school  learning  environments and  learning motivation on the independence of learning Islamic Religious Education on students  at SD Negeri 14 Bengkulu Selatan. With correlation  coefficient between  X2 and Y equal to 0,787  which show strong correlation  and correlation  equal to 62,0%.  Thirdly, there is simultaneously an influence between  school learning environment and learning motivation toward self-reliance learning of Islamic Religious Education in SD Negeri 14 Bengkulu  Selatan  with correlation  coefficient between  X1 and  X2 together  to Y equal  to 0,808  which shows at very strong relation level with correlation  equal  to 65 , 4% and  Y regression  result of X1 and X2, regression  equation obtained Y = 5,498  + 0,229  + 0,627